Effect of various techniques of Anesthesia in elective Caesarian section on short term Neonatal outcome - Durga Kosam; Ajay Kosam; M Madhumita Murthy (International Journal of Medical Research and Review, 2014)
Introduction: The basic aim of obstetric anesthesia is to provide adequate maternal pain relief with no deleterious effect on mother and newborn. This study aimed to assess the effect of spinal anesthesia, epidural anesthesia and general anesthesia using thiopentone sodium as induction agent on neonates delivered after elective caesarian section.Materials and methods: This is a prospective descriptive study at a tertiary care teaching hospital from June 2013 to May 2014. 60 cases of elective caesarian section admitted in Department of Obstetrics and Gynecology were studied. Patients were randomly divided into 3 groups each of 20 cases. Group 1 received spinal anesthesia, group 2 epidural anesthesia and group 3 general anesthesia. Neonatal outcome was assessed in relation to anesthetic techniques used.Results: The mean Apgar score at 1 min was lower in GA group (7 +/- 1.025) than in spinal anesthesia group (8.1+/- 0.78) and epidural anesthesia group (8.35 +/- 0.745). Total 3/60 (5%) neonates required resuscitation at birth all of which were in GA group. Induction delivery interval of < 5 min and > 20 min was associated with need for resuscitation at birth. Moderate depression of neonates (1 min Apgar score of 4-6) was observed in 2/20 (10%) neonates in group 3.Conclusion: Neonates born by elective LSCS under GA have lower 1 min Apgar scores. Induction delivery interval of < 5 min and > 20 min is associated with need for resuscitation at birth in neonates in GA group. These effects can be minimized by maintaining the ID interval between 5 – 15 minutes.